THE POLICY FORMULATION PROCESS OF DISASTER-RESPONSIVE VILLAGE REGULATIONS IN PABUARAN VILLAGE, LEBAK REGENCY - Rachmawati , Emi; Adimanggala, Rangga Muhammad (Journal of Indonesian Rural and Regional Government, 2023)
his study explores the policy formulation process of disaster-responsive village regulations in Pabuaran Village, Lebak Regency, using a qualitative descriptive method and the Backcasting framework. The research aims to understand how democratic values, implementation challenges, and technological support interact in shaping effective local policies. Data were collected through interviews and direct observation, focusing on the Village Regulation concerning Disaster Management. The Backcasting method, which emphasizes vision, present conditions, and priority setting, was applied to analyze the strategic planning process. Findings reveal that while Pabuaran Village has articulated a clear vision of resilience, it faces significant challenges including limited infrastructure, low public awareness, and minimal community involvement. However, the use of digital platforms has enhanced transparency and civic engagement. The study concludes that participatory governance, supported by strategic foresight and technological innovation, is essential for developing responsive and sustainable village regulations. This approach not only strengthens local disaster preparedness but also promotes inclusive and democratic governance.